Will vaccination against human papillomavirus prevent eye disease? A review of the evidence. Issue 4 (27th March 2008) - Hughes, D S; Powell, N; Fiander, A N
Abstract : The role of human papillomavirus (HPV) infection in eye disease is controversial. However, a recent case illustrates the possible role of HPV in conjunctival squamous carcinoma and the potentially devastating effects of this disease. The development of two vaccines to prevent infection with HPV types most commonly associated with anogenital cancers has led to debate about the pros and cons of a national immunisation programme to prevent cervical cancer. The introduction of such a vaccination programme may have an additional beneficial effect on the occurrence of some head and neck, including ocular, cancers. This review discusses the nature of papillomaviruses, mechanisms of infection and carcinogenesis, the possible role of HPV in eye disease, and finally the likely impact of the new prophylactic vaccines.